Entrepreneurs' Human Capital and Heterogeneous Labor Demand of Newly Established Firms - Kathrin Müller (Verein für Socialpolitik, 2010)
This paper investigates the effect of founders' human capital on the qualification structure of employees in newly established firms. Different corner solution outcome models are compared regarding their goodness of fit and adequacy. Based on survey data of about 1,200 new-born firms in the research- and knowledge-intensive industries in Germany, I find that industry experience and the educational degree largely determine the share of high-educated workers and the share of low-educated workers in young firms. Furthermore, this study provides evidence for a skill-biased technical change and a capital-skill complementarity in young firms.
Keywords: J23; J24; M13; 330; heterogeneous labor demand; human capital; start-ups